2019
DOI: 10.1002/adsc.201901252
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Active Site of an (S)‐Selective Amine Transaminase for Acceptance of Doubly Bulky Primary Amines

Abstract: A protein engineering approach for expanding the substrate scope of the (S)‐selective Chromobacterium violaceum amine transaminase is presented. Amino acid residues in the small binding pocket of the active site were targeted in order to increase the pocket size for acceptance of primary amines bearing two bulky groups. A highly sensitive fluorescence assay was then used to evaluate the generated enzyme variants for their activity towards propyl‐ and benzyl‐substituted screening substrates. The best variant, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…The TR 8 activity decreased by 49% in the presence of 50% (v/v) DMSO. Similar stability patterns have been observed using other ω-TAs during the production of chiral amines [45,46]. A concentration of 25% (v/v) DMSO was thus selected for subsequent experiments for bioprocess development.…”
Section: Bioconversion Conditionssupporting
confidence: 59%
“…The TR 8 activity decreased by 49% in the presence of 50% (v/v) DMSO. Similar stability patterns have been observed using other ω-TAs during the production of chiral amines [45,46]. A concentration of 25% (v/v) DMSO was thus selected for subsequent experiments for bioprocess development.…”
Section: Bioconversion Conditionssupporting
confidence: 59%
“…Similarly, the best variant of CvTA possessed the corresponding mutation F88L and exhibited 99% conversion in the synthesis of 1b. Other small residues that improved activity in the synthesis of bulky amines when replacing Phe86 are Ala 11,18,60 and Val. 15 The computational approach presented in this work avoids multiple design iterations and instead uses the Rosetta energy function in a single dock-and-design step.…”
Section: ■ Discussionmentioning
confidence: 99%
“… 10 This approach of rational design based on structural analysis was employed to redesign an ω-TA from Chromobacterium violaceum ( Cv TA) (PDB 4A6T) to obtain derivatives that are more suitable for the kinetic resolution of 1,2-diphenylethylamine. 11 The active site architecture was investigated, and two positions in the small binding pocket were identified as potential targets for mutagenesis. A double mutant with 30-fold higher activity than the wild-type enzyme was identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although yet a pipe dream, recent protein engineering initiatives have already shown that enzymatic transamination of similarly bulky substrates is possible. 296,462 Coupling of biocatalytically generated amino acid (analogues) through enzymatic amide bond formation would mean yet another advancement in the sustainable nature of biocatalytic anti-viral drug production. Currently, coupling is generally Chart 13 Structures of cobicistat with its morpholine-based amino acid highlighted in blue (A) and (1R,2S)-1-aminocyclopropanecarboxylic acid (ACCA) derivatives (B).…”
Section: Emerging Enzyme Classes -Challenges and Opportunities In Thementioning
confidence: 99%